2017
DOI: 10.1002/pbc.26858
|View full text |Cite
|
Sign up to set email alerts
|

Proton therapy for pediatric head and neck malignancies

Abstract: In this study, we report low rates of acute toxicity in a cohort of pediatric patients with head and neck malignancies. PBT appears safe for this patient population, with local control rates similar to historical reports. Longer follow-up will be required to evaluate late toxicity and long-term disease control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 41 publications
(76 reference statements)
1
17
0
Order By: Relevance
“…Another recent study investigated acute toxicities and early outcomes following PRT for pediatric head and neck malignancies. 26 That study concluded that PRT appears safe for this patient population, with LC rates similar to historical reports. However, due to limited follow-up time and cases, most studies are unable to provide sound data on long-term treatment-related side effects, such as growth and development impairment and secondary malignancies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Another recent study investigated acute toxicities and early outcomes following PRT for pediatric head and neck malignancies. 26 That study concluded that PRT appears safe for this patient population, with LC rates similar to historical reports. However, due to limited follow-up time and cases, most studies are unable to provide sound data on long-term treatment-related side effects, such as growth and development impairment and secondary malignancies.…”
Section: Discussionsupporting
confidence: 65%
“…After a median five‐year follow‐up time, the five‐year failure‐free survival estimate was 59% (95% confidence interval, 33%–79%), and the OS estimate was 64% (95% confidence interval, 37%–82%), which is comparable with that in historical controls. Another recent study investigated acute toxicities and early outcomes following PRT for pediatric head and neck malignancies . That study concluded that PRT appears safe for this patient population, with LC rates similar to historical reports.…”
Section: Discussionmentioning
confidence: 99%
“…18 A study by Vogel et al at the University of Pennsylvania treating 69 pediatric and AYA patients with primary jaw tumors found that proton beam therapy was associated with reduced acute toxicity, favorable local control, and improved OS rates, although further surveillance is needed to monitor for late effects and to evaluate local control outcomes. 5…”
Section: The Role Of Systemic Therapy In Oral Maxillofacial Tumorsmentioning
confidence: 99%
“…Morbidities include dermatitis with subsequent feeding intolerance, infection, craniofacial and dental anomalies, cataracts, neuroendocrine defects, and neurocognitive delays. 5 In addition, as a consequence of either systemic chemotherapy or radiation therapy, these patients are at increased risk for secondary malignancies. These short-and long-term morbidities present challenges when balanced against effective treatment of the patient's disease.…”
Section: Introductionmentioning
confidence: 99%
“…The high-dose deposition at the distal end followed by a steep decline as well as minimal lateral scattering allows superior tissue sparing and a dose reduction outside the planned margin [5]. The reduced volume of healthy tissue exposed to intermediate and low doses suggests a reduced risk of secondary malignancies accompanied by a reduced co-irradiation of dose-limiting organs-at-risk such as brain stem, spinal cord, oral cavity, or the optic nerve [6,7]. Hence, current treatment decisions for particle beam therapy are primarily based on vulnerable tumor locations near organs-at-risk, and treated entities comprise uveal melanoma, skull-based and intracranial tumors, prostate and head and neck tumors [8,9].…”
Section: Introductionmentioning
confidence: 99%